PREDIKSI HARGA LAPTOP MENGGUNAKAN ALGORITMA MULTIPLE LINEAR REGRESSION - Aldiriansyah Dwi Febrianto (2023)
Owning a laptop is more desirable for most people because it is more flexible than having a computer that can only be used at home. The number of brands offered triggers the growth of laptop price competition in meeting consumer needs. This research was conducted to find out the application in predicting the price of a laptop using a multiple linear regression algorithm. MLR is one of the statistical methods used to determine the functional relationship of a dependent variabel with two or more independent variables. MLR is used because it can predict continuous values such as prices. The data used contain 6 brands with a total of 160 data about laptop specifications such a Brand, Processor, RAM, GPU, Display and Storage. The prediction results using R Squared obtained a value of 0.74695 which satisfies the moderate correlation hypothesis and the Mean Absolute Percentage Error value is included in reasonable forecasting category with a score of 30.4356%.